Achieving social equality through community-led strategies: an analysis of inclusive communication practices - Handi Wijaya; La Mani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Social equality for people with hearing impairments remains a challenge due to communication barriers, social stigma, and limited access to information. Despite the growing emphasis on inclusive communication in disability advocacy, there is still limited research on how community-based initiatives implement these strategies and their impact. This study aims to analyze the role of inclusive communication strategies employed by the Sunyi Bermakna community in promoting social equality for people with hearing impairments. This research uses a qualitative case study approach. Data were collected through in-depth interviews, participatory observation, and documentation analysis, and analyzed using thematic analysis. The findings indicate that inclusive communication strategies such as the use of sign language, visual messaging, accessible social media content, and cross-community collaboration enhance public awareness and participation. For example, the use of subtitles and sign language in digital campaigns increased audience engagement and improved message accessibility, while collaborative initiatives expanded advocacy reach. However, this study is limited to a single community and lacks quantitative measurement of impact. Overall, inclusive communication plays a significant role not only in information delivery but also in fostering social inclusion and equality.